2013 IEEE/AIAA 32nd Digital Avionics Systems Conference (DASC) 2013
DOI: 10.1109/dasc.2013.6712517
|View full text |Cite
|
Sign up to set email alerts
|

Strategic airspace constraint analysis and environmental impact of Dynamic Weather Routes

Abstract: This paper presents analyses of the strategic airspace constraints and the environmental impact of Dynamic Weather Routes automation. The Dynamic Weather Routes are flight plans along which an aircraft can save a user-specified amount of windcorrected flying time compared to the currently active flight plan. The strategic airspace constraints address sector congestion and Special Activity Area traversal along the two flight plans. The environmental impact considers fuel burn and emissions (e.g., hydrocarbons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…To do so would also be beneficial for the environment due to reduced emissions. The Dynamic Weather Routes (DWR) automation has been developed and tested for Fort Worth Center (ZFW), as presented in McNally et al 1 , and Sheth et al 2,3 McNally et al 1 developed DWR for near-term, trajectory-based D https://ntrs.nasa.gov/search.jsp?R=20140010350 2019-06-29T00:14:39+00:00Z…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so would also be beneficial for the environment due to reduced emissions. The Dynamic Weather Routes (DWR) automation has been developed and tested for Fort Worth Center (ZFW), as presented in McNally et al 1 , and Sheth et al 2,3 McNally et al 1 developed DWR for near-term, trajectory-based D https://ntrs.nasa.gov/search.jsp?R=20140010350 2019-06-29T00:14:39+00:00Z…”
Section: Introductionmentioning
confidence: 99%
“…4 The air traffic manager would find this beneficial during severe weather events because regions of airspace in the vicinity of weather become congested. Sheth et al 2,3 demonstrated that the proposed weather avoidance concept helps alleviate congestion by directing some flights along dynamically generated weather avoidance routes, and reduces environmental impact of flights. However, this work has focused on one Center and the benefits of DWR automation at a national level have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%